Meningkatkan Kemampuan Mengenal Lambang Bilangan 1-5 Melalui Media Pohon Angka pada Anak Disabilitas Rungu - Ligustiana, Gita; Zulmiyetri, Zulmiyetri; Rahmahtrisilvia, Rahmahtrisilvia; Taufan, Johandri (Indo-MathEdu Intellectuals Journal, 2025)
The background of this research is the less-than-optimal learning process for recognizing number symbols 1-5 at SLB Haropana Hilmi. This study aims to improve the ability to recognize number symbols 1-5 through the use of the number tree media. The method used is classroom action research, consisting of two cycles. Each cycle includes four meetings with stages comprising planning, implementation, observation, and reflection. Data collection techniques include observation, performance assessment, and documentation. The results of the study indicate that: (1) The learning process for recognizing number symbols 1-5 improved through the use of the number tree media, and (2) The ability of deaf children to recognize number symbols 1-5 increased. This is evident from the comparison of student scores before and after the intervention. Before the intervention, MF and NS both scored 33%. After the first cycle of intervention, their scores improved to 67%. The study continued to the second cycle to further enhance students' abilities, resulting in final scores of 100% for MF and 89% for NS. It can be concluded that the number tree media can enhance the ability of deaf children to recognize number symbols 1-5.